2013
DOI: 10.2174/18715206113139990114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR Signaling by Quercetin in Cancer Treatment and Prevention

Abstract: Quercetin is an abundant micronutrient in our daily diet. Several beneficial health effects are associated with the dietary uptake of this bioflavonoid, including alleviating effects on chronic inflammation and atherosclerosis. A variety of in vitro data indicate a possible use of quercetin for cancer treatment purposes through its interaction with multiple cancer-related pathways. Among these, recent data reveal that quercetin can inhibit mTOR activity in cancer cells. Inhibition of the mTOR signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 0 publications
0
64
0
3
Order By: Relevance
“…Note that by day 3, proliferating preadipocytes increased by 2-5-fold in number vs. day 0 in the presence of D. The viability of nondividing, senescent preadipocytes from the same subjects decreased by 30–40% in the presence of 50 n m or greater D, indicating selective reduction in the viability of senescent cells. Q, a natural flavonol, inhibits PI3K, other kinases, and serpines (Olave et al ., 2010; Bruning, 2013). In contrast to D, at low concentrations, Q reduced the viability and caused cell death of senescent HUVECs to a greater extent than proliferating cells, but was less effective on preadipocytes (Fig 2…”
Section: Resultsmentioning
confidence: 99%
“…Note that by day 3, proliferating preadipocytes increased by 2-5-fold in number vs. day 0 in the presence of D. The viability of nondividing, senescent preadipocytes from the same subjects decreased by 30–40% in the presence of 50 n m or greater D, indicating selective reduction in the viability of senescent cells. Q, a natural flavonol, inhibits PI3K, other kinases, and serpines (Olave et al ., 2010; Bruning, 2013). In contrast to D, at low concentrations, Q reduced the viability and caused cell death of senescent HUVECs to a greater extent than proliferating cells, but was less effective on preadipocytes (Fig 2…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have suggested that several flavonoid compounds such as rutin and quercetin have strong antioxidant and anti-proliferative activities [5,6]. Recently, quercetin has attracted considerable attention as a potential anti-cancer agent and an inducer of autophagy [7,8]. Quercetin, as one of the most common flavonoids in nature, has been extensively studied as a chemoprevention agent in several cancer models due to its potent antioxidant, anti-tumor, and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found that quercetin, kaempferol and progesterone acted on 162, 71 and 112 targets, respectively, and therefore could be the crucial pleiotropically active compounds for TFS owing to their crucial positioning in the network. Previously, several studies demonstrated that quercetin inhibited inflammation, enhanced immune function and promoted apoptosis by modulating key pathways regulating cancer, such as, prostaglandin G/H synthase 2, interleukin (IL)-2, peroxisome proliferator activated receptor gamma and caspase-9 [26, 27]. …”
Section: Resultsmentioning
confidence: 99%